2010
DOI: 10.1088/0953-8984/22/26/263001
|View full text |Cite
|
Sign up to set email alerts
|

Atomic resolution non-contact atomic force microscopy of clean metal oxide surfaces

Abstract: In the last two decades the atomic force microscope (AFM) has become the premier tool for topographical analysis of surface structures at the nanometre scale. In its ultimately sensitive implementation, namely dynamic scanning force microscopy (SFM) operated in the so-called non-contact mode (NC-AFM), this technique yields genuine atomic resolution and offers a unique tool for real space atomic-scale studies of surfaces, nanoparticles as well as thin films, single atoms and molecules on surfaces irrespective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 235 publications
4
67
0
Order By: Relevance
“…by contact with the surface. 17,41 Previous studies have shown elegantly how differently terminated AFM tips may be used to identify and discriminate between the separate sublattices of some ionic compounds, such as KBr, 42 NaCl, 43 and CaF 2 . …”
Section: Nc-afm Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…by contact with the surface. 17,41 Previous studies have shown elegantly how differently terminated AFM tips may be used to identify and discriminate between the separate sublattices of some ionic compounds, such as KBr, 42 NaCl, 43 and CaF 2 . …”
Section: Nc-afm Simulationsmentioning
confidence: 99%
“…14,16 Using lowenergy ion scattering (LEIS), van der Laag et al investigated the relative amount of Mg and Al atoms in the surface layer of cleaved MgAl 2 O 4 (100) and compared those findings with DFT simulations to show that fractured surfaces expose a surplus of Mg, reflecting an Mg-terminated surface. Atomic force microscopy (AFM) studies operated in the so-called noncontact mode (NC-AFM) have recently been successfully employed for atomic-scale studies of a range of clean metal oxide insulating surfaces, [17][18][19] such as α-Al 2 O 3 (0001) [20][21][22] or MgO. 23,24 Very recently, we used NC-AFM to resolve the atomic-scale surface structure of the MgAl 2 O 4 (100) surface.…”
Section: Introductionmentioning
confidence: 99%
“…Since the interaction of the tip and the surface is so strong, the deformation of a soft sample typically occurs, and as the results of it, the soft sample may be damaged or moved by the sharp tip. Schematically, this deformation is occurred in the top right cartoon by displacement of the red spheres 3 . For hard samples at small tip-surface separation, the pressure created by the tip at the apex is so large that atoms can jump from tip to surface and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1B illustrates the major operation modes of the AFM. The manner of the microscope operation corresponding to the attraction part of the tip-sample interaction potential is noncontact mode (NC-AFM) 3 . A breakthrough in the high-resolution AFM imaging was made with implementation of the NC-AFM mode, offering a unique tool for real space atomicscale studies of surfaces and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, thanks to the development of the noncontact operation mode of AFM (NC-AFM) [4][5][6][7] based on a frequencymodulation approach involving oscillating cantilevers [8], true atomic-resolution imaging was achieved over the last two decades on a large array of material surfaces, ranging from ionic crystals [9][10][11], metals [12][13][14] and metal oxides [15] to the new class of two-dimensional materials, including graphene [16,17] and silicene [18].…”
mentioning
confidence: 99%